Hard carbon material, secondary battery and electronic device
By using hard carbon materials with a sheet-like structure to adjust their size to improve the contact between particles, the problems of low compaction density and poor contact in secondary batteries are solved, and the effect of improving the energy density and performance of the battery is achieved.
Patent Information
- Application Number
- CN202411854039.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-16
AI Technical Summary
The existing hard carbon materials have problems such as low compaction density and poor contact between particles in secondary batteries, resulting in poor capacity, circulation and rate performance.
A hard carbon material with a sheet-like structure is used to regulate its length (2μm≤L≤16μm) and width (0.1μm≤D1≤3μm), so as to improve the contact and processing performance between particles, enhance the electronic and ionic conductance, and improve the dynamic process and cyclic stability of the battery.
Through the use of sheet-like hard carbon materials, the compaction density of the battery pole plate is improved, the electrode sheet resistance is reduced, and the energy density, rate performance and cycling performance of the secondary battery are improved.
Smart Images

Figure CN119725524A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of electrochemical technology, and in particular to a hard carbon material, a secondary battery and an electronic device. Background Art
[0002] With the rapid development of electric vehicles and mobile electronic devices in recent years, people have increasingly higher demands on the energy density, safety, and cycle performance of secondary batteries (e.g., lithium-ion batteries). The design of new secondary batteries with improved comprehensive performance is the key to meeting the growing demand. Improving the composition and structure of electrode active materials in secondary batteries by design is one of the effective methods to improve the rapid charge and discharge performance and cycle performance of batteries, and is also the key to obtaining high-safety, high-energy-density batteries.
[0003] Negative electrode active materials account for 5%-15% of the battery cost and are one of the four main materials in the battery system. Graphite, as the most commonly used negative electrode material for lithium-ion batteries, has the advantages of stable charging and discharging platform and high efficiency, but its capacity development has reached its limit. Therefore, there is an urgent need to develop an improved negative electrode to further solve the problems currently faced by graphite negative electrodes. Hard carbon materials have attracted great attention due to their high theoretical capacity, low volume expansion and rapid charging and discharging. However, the inherent hard skeleton and high porosity of hard carbon particles lead to low compaction density and poor contact between particles in hard carbon materials, resulting in poor capacity, cycle performance and rate performance of secondary batteries. Summary of the invention
[0004] The object of the present application is to provide a hard carbon material, a secondary battery and an electronic device in an attempt to solve at least one problem existing in the related art to at least some extent.
[0005] According to the first aspect of the present application, the present application provides a hard carbon material, the hard carbon material is in a sheet structure, the length of the sheet structure is L, the width of the sheet structure is D1, wherein L satisfies: 2μm≤L≤16μm; D1 satisfies: 0.1μm≤D1≤3μm. The length and width of the sheet hard carbon material provided in the present application will affect the stacking state between particles, and thus affect the mass transfer process of the electrochemical reaction. When the length of the sheet hard carbon material is within the above range, the sheet hard carbon material can be used alone or in combination with negative electrode active materials such as graphite materials. It can contact with multiple particles at the same time, enhance the electronic conductivity and ion conductivity between particles, thereby accelerating the kinetic process of the battery and improving the rate performance; when the width of the sheet hard carbon material is within the above range, it can improve the processing performance of the material, so that the pole piece has good bonding performance, thereby improving the cycle stability of the secondary battery. That is, by regulating the length, width and other parameters of the flaky hard carbon material of the present application within the above-mentioned range, the hard carbon materials can have good contact and better processing performance, the compaction density of the battery pole piece can be increased, and the pole piece resistance can be reduced, thereby increasing the energy density of the secondary battery while improving the rate performance and cycle performance of the secondary battery.
[0006] In some embodiments of the present application, the hard carbon material satisfies at least one of the following conditions:
[0007] (1) The length L of the sheet structure satisfies: 2 μm ≤ L ≤ 15 μm;
[0008] (2) The width D1 of the sheet structure satisfies: 0.5 μm ≤ D1 ≤ 1.9 μm;
[0009] (3) The height H1 of the sheet structure satisfies: 0.02 μm ≤ H1 ≤ 2.5 μm; or, 0.05 μm ≤ H1 ≤ 1.9 μm;
[0010] (4) The ratio of the length L of the sheet structure to the height H1 of the sheet structure satisfies: 2.5≤L / H1≤750; or, 2.5≤L / H1≤200;
[0011] (5) The ratio of the width D1 of the sheet structure to the height H1 of the sheet structure satisfies: 1≤D1 / H1≤12.
[0012] In some embodiments of the present application, the length L of the sheet structure satisfies: 2 μm ≤ L ≤ 15 μm. When the length of the sheet-like hard carbon material provided in the present application is within the above range, the sheet-like hard carbon material, when used alone or in combination with negative electrode active materials such as graphite materials, can further contact with multiple particles at the same time, further enhancing the electronic conductivity and ionic conductivity between the particles, thereby accelerating the kinetic process of the battery and further improving the rate performance.
[0013] In some embodiments of the present application, the width D1 of the sheet structure satisfies: 0.5 μm ≤ D1 ≤ 1.9 μm. When the width of the sheet-like hard carbon material provided in the present application is within the above range, the processing performance of the material can be further improved, so that the pole piece has good bonding performance, thereby further improving the cycle stability of the secondary battery.
[0014] In some embodiments of the present application, the height H1 of the sheet structure satisfies: 0.05μm≤H1≤2.5μm. Preferably, the height H1 of the sheet structure satisfies: 0.05μm≤H1≤1.9μm. When the height of the flaky hard carbon material provided in the present application is within the above range, a certain toughness can be given to the particles, so that the material can bend to a certain extent. When the material is used alone or in combination with negative active materials such as graphite materials, it can contact multiple surfaces of the particles at the same time, thereby effectively reducing the interface impedance and improving the rate performance of the secondary battery.
[0015] In some embodiments of the present application, the ratio of the length L of the sheet structure to the height H1 of the sheet structure satisfies: 2.5≤L / H1≤750; preferably, the ratio of the length L of the sheet structure to the height H1 of the sheet structure satisfies 2.5≤L / H1≤200. When the ratio of the length L to the height H1 of the sheet-like hard carbon material provided in the present application is within the above range, the rate performance of the secondary battery can be further improved.
[0016] In some embodiments of the present application, the ratio of the width D1 of the sheet structure to the height H1 of the sheet structure satisfies: 1≤D1 / H1≤12. When the ratio of the width D1 to the height H1 of the sheet-like hard carbon material provided in the present application is within the above range, the cycle performance and rate performance of the secondary battery can be further improved.
[0017] In some embodiments of the present application, the length L of the sheet structure is composed of three parts: the length of the left curved surface L1, the length of the square area L2, and the length of the right curved surface L3. The relationship between L1, L2, and L3 satisfies: 2μm≤L1+L2+L3≤16μm, 0.01μm≤L1≤1.5μm, and 10≤L2 / L1≤80. The morphology of the curved surfaces on both sides of the hard carbon material is affected by the synthesis conditions. The curved surfaces with different structures will affect the stacking state between the sheet structures. The existence of the curved surface structure can relieve the internal stress formed during the particle stacking process and avoid particle crushing. At the same time, the accumulation of multiple curved surfaces is easy to form a small amount of pores, which can store electrolytes and improve the wettability of active substances to electrolytes. By regulating the length of the left curved surface, the length of the square area, and the length of the right curved surface of the sheet structure of the hard carbon material of the present application within the above range, the hard carbon materials can have good contact with each other, the compaction density of the battery pole piece can be improved, and the energy density of the secondary battery can be improved.
[0018] In some embodiments of the present application, the hard carbon material satisfies at least one of the following conditions:
[0019] (6) 2μm≤L1+L2+L3≤15μm;
[0020] (7) 0.05 μm ≤ L1 ≤ 1 μm;
[0021] (8)11≤L2 / L1≤38.
[0022] In some embodiments of the present application, the hard carbon material satisfies: 2 μm ≤ L1 + L2 + L3 ≤ 15 μm.
[0023] In some embodiments of the present application, the hard carbon material satisfies: 0.05 μm ≤ L1 ≤ 1 μm.
[0024] In some embodiments of the present application, the hard carbon material satisfies: 11≤L2 / L1≤38.
[0025] By regulating the left arc length, square area length and right arc length of the hard carbon material sheet structure of the present application within the above range, it is possible to further promote good contact between the hard carbon materials, thereby improving the compaction density of the battery electrode and the energy density of the secondary battery.
[0026] In some embodiments of the present application, the hard carbon material satisfies at least one of the following conditions:
[0027] (9) 0.8 μm ≤ L2 ≤ 15 μm; or, 1.9 μm ≤ L2 ≤ 13 μm;
[0028] (10) 0.05 μm ≤ L3 ≤ 1.5 μm; or, 0.05 μm ≤ L3 ≤ 1 μm.
[0029] In some embodiments of the present application, the square area length L2 of the hard carbon material satisfies: 1.9 μm ≤ L2 ≤ 13 μm. Alternatively, 1.9 μm ≤ L2 ≤ 13 μm. When the length L2 of the material is controlled within the above range, the material can be in contact with multiple particles at the same time when used alone or in combination with negative electrode active materials such as graphite materials, thereby enhancing the electronic conductivity and ionic conductivity between particles, thereby accelerating the kinetic process of the battery and improving the rate performance.
[0030] In some embodiments of the present application, the length L3 of the right side arc of the sheet structure satisfies: 0.05 μm ≤ L3 ≤ 1 μm; or, 0.05 μm ≤ L3 ≤ 1 μm. The existence of the arc structure can relieve the internal stress formed during the particle accumulation process and avoid particle breakage. At the same time, the accumulation of multiple arcs can easily form a small amount of pores, which can store electrolyte and improve the wettability of active materials to the electrolyte.
[0031] In some embodiments of the present application, the closed pore volume of the sheet structure is 0.01 to 0.4 cm 3 In some embodiments of the present application, the closed pore volume of the sheet structure is 0.05 to 0.28 cm 3 / g. The increase in the closed pore content in the hard carbon material helps to store more active metal ions, thereby improving the active metal ion storage capacity. However, too many closed pores will reduce the density of the particles, and there is a risk of the closed pores becoming larger, which is not conducive to energy storage. The present application controls the closed pore volume in the hard carbon material within the above range, so that the hard carbon material can obtain a higher capacity and the active material has a lower energy storage platform, thereby improving the energy density of the secondary battery.
[0032] In some embodiments of the present application, the hard carbon material satisfies at least one of the following conditions:
[0033] (11) The surface of the sheet structure also has a carbon coating layer;
[0034] (12) The surface of the sheet structure also has a carbon coating layer, and the thickness of the carbon coating layer ranges from 20 to 100 nm;
[0035] (13) The sheet structure contains a first element, and the first element includes any one of Li, Na, K, Rb, Mg, Ca, and Zn;
[0036] (14) The sheet structure contains a first element, the first element includes any one of Li, Na, K, Rb, Mg, Ca, and Zn; the content of the first element relative to the total mass of the hard carbon material is 0.01% to 0.9%;
[0037] (15) The specific surface area of the sheet material is in the range of 2 to 28 m 2 / g;
[0038] (16) The ID / IG value of the sheet material is 1.0 to 1.3.
[0039] In some embodiments of the present application, in the hard carbon material, the surface of the sheet structure also has a carbon coating layer. Coating the carbon layer on the hard carbon surface helps to reduce sheet surface defects, while reducing the exposure of sheet pore structure, improving the first coulomb efficiency of the negative electrode active material, so that the negative electrode active material has a high reversible capacity, thereby improving the energy density and cycle stability of the secondary battery.
[0040] In some embodiments of the present application, in the hard carbon material, the surface of the sheet structure also has a carbon coating layer, and the thickness of the carbon coating layer ranges from 20 to 100 nm. Coating the surface of the hard carbon material with a carbon layer and controlling the thickness of the carbon coating layer within the above range helps to further reduce sheet surface defects, while further reducing the exposure of sheet pore structures, further improving the first coulomb efficiency of the negative electrode active material, so that the negative electrode active material has a high reversible capacity, thereby improving the energy density and cycle stability of the secondary battery.
[0041] In some embodiments of the present application, in the hard carbon material, the sheet structure contains a first element, and the first element includes any one of Li, Na, K, Rb, Mg, Ca, and Zn. By introducing the first element into the sheet structure of the hard carbon material, active metal ions can be induced to be stored in the hard carbon material, thereby improving the active metal ion storage capacity.
[0042] In some embodiments of the present application, in the hard carbon material, the sheet structure contains a first element, the first element includes any one of Li, Na, K, Rb, Mg, Ca, and Zn, and the content of the first element relative to the total mass of the hard carbon material is 0.01% to 0.9%. The present application can further induce the storage of active metal ions in the hard carbon material by regulating the content of the first element in the hard carbon material within the above range, further improving the storage capacity of active metal ions, and applying the hard carbon material of the present application to a secondary battery can help improve the gram capacity of the negative electrode of the battery, thereby improving the energy density of the secondary battery.
[0043] In some embodiments of the present application, in the hard carbon material, the specific surface area of the flake material is in the range of 2 to 28 m 2 / g. If the specific surface area of the hard carbon material is too large, active metal ions will be adsorbed on the surface of the material, and more electrolyte will be consumed to form a stable SEI layer, resulting in a decrease in the first coulombic efficiency of the material. The present application can avoid excessive electrolyte consumption by regulating the specific surface area of the hard carbon material within the above range, while ensuring the formation of a stable SEI, so that the hard carbon material has a higher reversible capacity and a higher first coulombic efficiency, thereby improving the energy density and cycle stability of the secondary battery.
[0044] In some embodiments of the present application, in the hard carbon material, the ID / IG value of the sheet structure is 1.0 to 1.3. ID is the peak area of the D peak in the Raman spectrum of the hard carbon material, and IG is the peak area of the G peak in the Raman spectrum of the hard carbon material. The ID / IG value of the hard carbon material provided by the present application is regulated within the above range, so that the hard carbon material has a suitable degree of defects, which can further promote ion adsorption and bonding, while reducing the irreversible capacity loss caused by a high degree of defects, thereby facilitating the improvement of the gram capacity of the hard carbon material.
[0045] According to the second aspect of the present application, the present application further provides a negative electrode plate, the negative electrode plate comprising a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, the negative electrode active material layer comprising a negative electrode active material, the negative electrode active material comprising any hard carbon material described in the first aspect of the present application. The negative electrode plate comprising the above hard carbon material has high capacity, good interface adhesion and high compaction density, and is applied to a secondary battery, which can improve the energy density of the secondary battery while improving the cycle performance and rate performance of the secondary battery.
[0046] In some embodiments of the present application, the negative electrode active material includes any hard carbon material and graphite material described in the first aspect of the present application. Graphite generally has a higher compaction density, but the specific capacity of graphite is low and the rate performance is poor. The hard carbon material has a higher specific capacity, but the compaction density is relatively low. The present application obtains a negative electrode material with both high capacity and high compaction by compounding the hard carbon material with the graphite material, and obtains a negative electrode active material layer with both high capacity and high compaction density. Ordinary granular hard carbon is not conducive to the compounding of hard carbon materials with negative electrode active materials such as graphite. The flaky hard carbon material provided by the present application increases the contact between hard carbon particles and between hard carbon and graphite particles, which is beneficial to reduce the electrode sheet resistance and further improves the rate performance of the negative electrode active material.
[0047] In some embodiments of the present application, the negative electrode active material includes any hard carbon material and graphite material described in the first aspect of the present application, and the mass percentage of the hard carbon material is 0.1% to 99.9% based on the total mass of the negative electrode active material. The present application regulates the relative proportion of flaky hard carbon and graphite in the composite pole piece, and by regulating the mass percentage of the hard carbon material in the negative electrode active material layer within the scope of the present application, the compaction density of the negative electrode active material layer can be optimized, thereby improving the energy density, rate performance and cycle retention rate of the secondary battery.
[0048] In some embodiments of the present application, the compaction density of the negative electrode active material layer is in the range of 1.0 to 1.9 g / cm 3By adjusting the compaction density of the negative electrode active material layer within the above range, the content of the negative electrode active material per unit area can be increased, thereby increasing the energy density of the secondary battery.
[0049] According to the third aspect of the present application, the present application provides a secondary battery, which includes the negative electrode sheet provided by any one embodiment of the second aspect of the present application. The secondary battery including the negative electrode sheet has high energy density and good cycle performance.
[0050] According to a fourth aspect of the present application, the present application provides an electronic device, which includes the secondary battery provided by any one embodiment of the third aspect of the present application. The electronic device including the secondary battery has a long service life. BRIEF DESCRIPTION OF THE DRAWINGS
[0051] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other embodiments can also be obtained based on these drawings.
[0052] Figure 1 A schematic diagram of the structure of a hard carbon material provided in an embodiment of the present application;
[0053] Figure 2 The charge and discharge curve of the negative electrode active material of Comparative Example 1-1 in the Li / Li+ potential range of 0V to 2.5V;
[0054] Figure 3 The charge and discharge curve of the negative electrode active material of Example 1-2 in the potential range of Li / Li+ from 0V to 2.5V;
[0055] Figure 4 1 is the charge and discharge curve of the negative electrode active material of Example 2-3 in the potential range of Li / Li+ from 0V to 2.5V. DETAILED DESCRIPTION
[0056] The following will be combined with the drawings in the embodiments of the present application to clearly and completely describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field based on the present application belong to the scope of protection of the present application.
[0057] It should be noted that in the specific implementation manner of the present application, the present application is explained by taking a lithium-ion battery as an example of a secondary battery, but the secondary battery of the present application is not limited to a lithium-ion battery.
[0058] As the most commonly used negative electrode material for lithium-ion batteries, graphite has the advantages of stable charging and discharging platform and high efficiency, but its capacity development has reached its limit. Therefore, it is urgent to develop an improved negative electrode to further solve the problems currently faced by graphite negative electrodes. Hard carbon materials have attracted great attention due to their high theoretical capacity, low volume expansion and rapid charge and discharge. However, the intrinsic hard skeleton and high porosity of hard carbon particles lead to problems such as low compaction density and poor contact between particles in hard carbon materials, and the capacity, cycle performance and rate performance of secondary batteries are poor. Based on this, the inventors started from the negative electrode active material itself and found through a lot of research that by preparing hard carbon materials with special morphology, by using them purely or in combination with commercial graphite, the problems of low gram capacity of negative electrode sheets, poor adhesion and poor conductivity can be solved, thereby increasing the compaction density of battery sheets, thereby increasing the energy density of secondary batteries and improving the rate performance and cycle performance of secondary batteries.
[0059] According to a first aspect of the present application, the present application provides a hard carbon material, the hard carbon material is in a sheet-like structure, the length of the sheet-like structure is L, the width of the sheet-like structure is D1, and the height of the sheet-like structure is H1, wherein L satisfies: 2μm≤L≤16μm; D1 satisfies: 0.1μm≤D1≤3μm. Specifically, the length L of the sheet-like structure can be 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, or a range consisting of any two of the above values. Specifically, the width D1 of the sheet structure can be 0.1μm, 0.2μm, 0.3μm, 0.4μm, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1.0μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm, 1.6μm, 1.7μm, 1.8μm, 1.9μm, 2.0μm, 2.1μm, 2.2μm, 2.3μm, 2.4μm, 2.5μm, 2.6μm, 2.7μm, 2.8μm, 2.9μm, 3μm or a range consisting of any two of the above values.
[0060] Specifically, the hard carbon material provided in the present application has a flaky structure, which means that in the SEM electron microscope image of the hard carbon material provided, it can be clearly observed that the hard carbon material has at least one particle with a flaky structure, and the particles with flaky structures can be stacked on each other. The length and width of the flaky hard carbon material provided in the present application will affect the stacking state between the particles, and thus affect the mass transfer process of the electrochemical reaction. When the length of the flaky hard carbon material is within the above range, the flaky hard carbon material can be used alone or in combination with negative electrode active materials such as graphite materials. It can contact with multiple particles at the same time, enhance the electronic conductivity and ion conductivity between particles, thereby accelerating the kinetic process of the battery and improving the rate performance; when the width of the flaky hard carbon material is within the above range, it can improve the processing performance of the material, so that the pole piece has good bonding performance, thereby improving the cycle stability of the secondary battery. That is, by regulating the length, width and other parameters of the flaky hard carbon material of the present application within the above-mentioned range, the hard carbon materials can have good contact and better processing performance, the compaction density of the battery pole piece can be increased, and the pole piece resistance can be reduced, thereby increasing the energy density of the secondary battery while improving the rate performance and cycle performance of the secondary battery.
[0061] In some embodiments of the present application, the hard carbon material satisfies at least one of the following conditions:
[0062] (1) The length L of the sheet structure satisfies: 2 μm ≤ L ≤ 15 μm;
[0063] (2) The width D1 of the sheet structure satisfies: 0.5 μm ≤ D1 ≤ 1.9 μm;
[0064] (3) The height H1 of the sheet structure satisfies: 0.02 μm ≤ H1 ≤ 2.5 μm; or, 0.05 μm ≤ H1 ≤ 1.9 μm;
[0065] (4) The ratio of the length L of the sheet structure to the height H1 of the sheet structure satisfies: 2.5≤L / H1≤750; or, 2.5≤L / H1≤200;
[0066] (5) The ratio of the width D1 of the sheet structure to the height H1 of the sheet structure satisfies: 1≤D1 / H1≤12.
[0067] In some embodiments of the present application, the length L of the sheet structure satisfies: 2 μm ≤ L ≤ 15 μm. When the length of the sheet-like hard carbon material provided in the present application is within the above range, the sheet-like hard carbon material, when used alone or in combination with negative electrode active materials such as graphite materials, can further contact with multiple particles at the same time, further enhancing the electronic conductivity and ionic conductivity between the particles, thereby accelerating the kinetic process of the battery and further improving the rate performance.
[0068] In some embodiments of the present application, the width D1 of the sheet structure satisfies: 0.5 μm ≤ D1 ≤ 1.9 μm. When the width of the sheet-like hard carbon material provided in the present application is within the above range, the processing performance of the material can be further improved, so that the pole piece has good bonding performance, thereby further improving the cycle stability of the secondary battery.
[0069] In some embodiments of the present application, the height H1 of the sheet structure satisfies: 0.05 μm ≤ H1 ≤ 2.5 μm. Specifically, the height H1 of the sheet structure can be 0.05 μm, 0.06 μm, 0.07 μm, 0.08 μm, 0.09 μm, 0.1 μm, 0.15 μm, 0.2 μm, 0.25 μm, 0.3 μm, 0.35 μm, 0.4 μm, 0.45 μm, 0.5 μm, 0.55 μm, 0.6 μm, 0.65 μm, 0.7 μm , 0.75μm, 0.8μm, 0.85μm, 0.9μm, 1.0μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm, 1.6μm, 1.7μm, 1.8μm, 1.9μm, 2μm, 2.1μm, 2.2μm, 2.3μm, 2.4μm, 2.5μm or a range consisting of any two of the above values. Preferably, the height of the sheet structure H1 satisfies: 0.05μm≤H1≤1.9μm. When the height of the flaky hard carbon material provided in the present application is within the above range, a certain toughness can be given to the particles, so that the material can bend to a certain extent. When the material is used alone or in combination with negative active materials such as graphite materials, it can contact multiple surfaces of the particles at the same time, thereby effectively reducing the interface impedance and improving the rate performance of the secondary battery.
[0070] In some embodiments of the present application, the ratio of the length L of the sheet structure to the height H1 of the sheet structure satisfies: 2.5≤L / H1≤750. Specifically, the ratio of the length L of the sheet structure to the height H1 of the sheet structure may be: 2.5, 3, 3.3, 4.0, 4.2, 4.5, 5.0, 5.5, 6.0, 7.0, 8.0, 9.0, 10.0, 10.3, 20, 30, 40, 50, 60, 70, 80, 90, 100, 150, 160, 170, 180, 187, 187.5, 190, 200, 210, 220, 225, 230, 240, 250, 260, 300, 400, 500, 600, 700, 750, or a range consisting of any two of the above values. Preferably, the ratio of the length L of the sheet structure to the height H1 of the sheet structure satisfies 2.5≤L / H1≤200. When the ratio of the length L to the height H1 of the sheet-like hard carbon material provided in the present application is within the above range, the rate performance of the secondary battery can be further improved.
[0071] In some embodiments of the present application, the ratio of the width D1 of the sheet structure to the height H1 of the sheet structure satisfies: 1≤D1 / H1≤12. Specifically, the ratio of the width D1 of the sheet structure to the height H1 of the sheet structure may be: 1, 1.07, 1.13, 1.15, 1.18, 1.2, 1.25, 1.30, 1.35, 1.40, 1.45, 1.50, 1.55, 1.60, 2.0, 3.0, 4.0, 5.0, 6.0, 7.0, 8.0, 9.0, 10.0, 11.0, 11.25, 11.35, 11.45, 11.65, 11.67, 12 or a range consisting of any two of the above values. When the ratio of the width D1 to the height H1 of the flaky hard carbon material provided in the present application is within the above range, the cycle performance and rate performance of the secondary battery can be further improved.
[0072] In some embodiments of the present application, the length L of the sheet structure is composed of three parts: the length L1 of the left curved surface, the length L2 of the square area, and the length L3 of the right curved surface. The relationship L1+L2+L3 among the length L1 of the left curved surface, the length L2 of the square area, and the length L3 of the right curved surface of the sheet structure satisfies: 2μm≤L1+L2+L3≤16μm, 0.01μm≤L1≤1.5μm, and 10≤L2 / L1≤80. Specifically, the relationship L1+L2+L3 among the length L1 of the left curved surface, the length L2 of the square area, and the length L3 of the right curved surface of the sheet structure can be: 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, 16μm, or a range consisting of any two of the above values. Specifically, the length L1 of the left curved surface of the sheet structure can be 0.01μm, 0.02μm, 0.03μm, 0.04μm, 0.05μm, 0.06μm, 0.07μm, 0.08μm, 0.09μm, 0.1μm, 0.15μm, 0.2μm, 0.25μm, 0.3μm, 0.35μm, 0.4μm, 0.45μm, 0.5μm, 0.55μm, 0.6μm, 0.65μm, 0.7μm, 0.75μm, 0.8μm, 0.85μm, 0.9μm, 1.0μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm or a range consisting of any two of the above values. Specifically, the ratio L2 / L1 of the square area length L2 of the sheet structure to the left curved surface length L1 can be 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41 , 42, 43, 44, 45, 46, 47, 48, 49, 50, 51, 52, 53, 54, 55, 56, 57, 58, 59, 60, 61, 62, 63, 64, 65, 66, 67, 68, 69, 70, 71, 72, 73, 74, 75, 76, 77, 78, 79, 80, or a range consisting of any two of the above values. The morphology of the arc surfaces on both sides of the hard carbon material is affected by the synthesis conditions. Arc surfaces with different structures will affect the stacking state between the sheet structures. The existence of the arc surface structure can alleviate the internal stress formed during the particle stacking process and avoid particle breakage. At the same time, the accumulation of multiple arc surfaces can easily form a small amount of pores, which can store electrolyte and improve the wettability of active substances to the electrolyte. By regulating the left arc surface length, square area length and right arc surface length of the sheet structure of the hard carbon material of the present application within the above range, the hard carbon materials can have good contact with each other, the compaction density of the battery electrode can be improved, and the energy density of the secondary battery can be improved.
[0073] In some embodiments of the present application, the hard carbon material satisfies at least one of the following conditions:
[0074] (6) 2μm≤L1+L2+L3≤15μm;
[0075] (7) 0.05 μm ≤ L1 ≤ 1 μm;
[0076] (8)11≤L2 / L1≤38.
[0077] In some embodiments of the present application, the hard carbon material satisfies: 2 μm ≤ L1 + L2 + L3 ≤ 15 μm.
[0078] In some embodiments of the present application, the hard carbon material satisfies: 0.05 μm ≤ L1 ≤ 1 μm.
[0079] In some embodiments of the present application, the hard carbon material satisfies: 11≤L2 / L1≤38.
[0080] By regulating the left arc length, square area length and right arc length of the hard carbon material sheet structure of the present application within the above range, it is possible to further promote good contact between the hard carbon materials, thereby improving the compaction density of the battery electrode and the energy density of the secondary battery.
[0081] In some embodiments of the present application, the hard carbon material satisfies at least one of the following conditions:
[0082] (9) 0.8 μm ≤ L2 ≤ 15 μm; or, 1.9 μm ≤ L2 ≤ 13 μm;
[0083] (10) 0.05 μm ≤ L3 ≤ 1.5 μm; or, 0.05 μm ≤ L3 ≤ 1 μm.
[0084] In some embodiments of the present application, the square area length L2 of the sheet structure satisfies: 0.8μm≤L2≤15μm. Specifically, the square area length L2 of the sheet structure can be: 0.8, 0.9, 1.0, 1.5, 1.9, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 4.6, 4.7, 4.8, 4.9, 5.0, 5.5, 6.0, 6.5, 6.6, 7.0, 7.5, 7.6, 8.0, 8.5, 9.0, 10.0, 10.4, 10.5, 11, 11.5, 12.0, 12.5, 13.0, 14.0, 15.0 or a range consisting of any two of the above values. Preferably, the square area length L2 of the sheet structure satisfies: 1.9μm≤L2≤13μm. By controlling the length L2 of the material within the above range, the material, when used alone or in combination with negative electrode active materials such as graphite, can contact multiple particles at the same time, enhancing the electronic conductivity and ionic conductivity between the particles, thereby accelerating the kinetic process of the battery and improving the rate performance.
[0085] In some embodiments of the present application, the length L3 of the right side arc surface of the sheet structure satisfies: 0.05μm≤L3≤1.5μm. Specifically, the length L3 of the right side arc surface of the sheet structure can be 0.05μm, 0.1μm, 0.2μm, 0.3μm, 0.4μm, 0.5μm, 0.6μm, 0.7μm, 0.8μm, 0.9μm, 1.0μm, 1.1μm, 1.2μm, 1.3μm, 1.4μm, 1.5μm or a range consisting of any two of the above values. Preferably, the length L3 of the right side arc surface of the sheet structure satisfies: 0.05μm≤L3≤1μm. The presence of the arc surface structure can alleviate the internal stress formed during the particle accumulation process and avoid particle breakage. At the same time, the accumulation of multiple arc surfaces can easily form a small amount of pores, which can store electrolyte and improve the wettability of active substances to electrolyte.
[0086] In some embodiments of the present application, the closed pore volume of the sheet structure is 0.01 to 0.4 cm 3 / g. Specifically, the closed pore volume of the sheet structure can be 0.01cm 3 / g, 0.02cm 3 / g, 0.03cm 3 / g, 0.04cm 3 / g, 0.05cm 3 / g, 0.06cm 3 / g, 0.07cm 3 / g, 0.08cm 3 / g, 0.09cm 3 / g, 0.1cm 3 / g, 0.12cm 3 / g, 0.15cm 3 / g, 0.2cm 3 / g, 0.21cm 3 / g, 0.24cm 3 / g, 0.25cm 3 / g, 0.28cm 3 / g, 0.3cm 3 / g, 0.35cm 3 / g, 0.4cm 3 / g or a range consisting of any two of the above values. Preferably, the closed pore volume of the sheet structure is 0.05-0.28 cm 3 / g. The increase in the closed pore content in the hard carbon material helps to store more active metal ions, thereby improving the active metal ion storage capacity. However, too many closed pores will reduce the density of the particles, and there is a risk of the closed pores becoming larger, which is not conducive to energy storage. The present application controls the closed pore volume in the hard carbon material within the above range, so that the hard carbon material can obtain a higher capacity and the active material has a lower energy storage platform, thereby improving the energy density of the secondary battery.
[0087] In some embodiments of the present application, the hard carbon material satisfies at least one of the following conditions:
[0088] (11) The surface of the sheet structure also has a carbon coating layer;
[0089] (12) The surface of the sheet structure also has a carbon coating layer, and the thickness of the carbon coating layer ranges from 20 to 100 nm;
[0090] (13) The sheet structure contains a first element, and the first element includes any one of Li, Na, K, Rb, Mg, Ca, and Zn;
[0091] (14) The sheet structure contains a first element, the first element includes any one of Li, Na, K, Rb, Mg, Ca, and Zn; the content of the first element relative to the total mass of the hard carbon material is 0.01% to 0.9%;
[0092] (15) The specific surface area of the sheet material is in the range of 2 to 28 m 2 / g;
[0093] (16) The ID / IG value of the sheet material is 1.0 to 1.3.
[0094] In some embodiments of the present application, in the hard carbon material, the surface of the sheet structure also has a carbon coating layer. Coating the carbon layer on the hard carbon surface helps to reduce sheet surface defects, while reducing the exposure of sheet pore structure, improving the first coulomb efficiency of the negative electrode active material, so that the negative electrode active material has a high reversible capacity, thereby improving the energy density and cycle stability of the secondary battery.
[0095] In some embodiments of the present application, in the hard carbon material, the surface of the sheet structure also has a carbon coating layer, and the thickness of the carbon coating layer ranges from 20 to 100 nm. Specifically, the thickness of the carbon coating layer can be 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm, 60 nm, 65 nm, 70 nm, 75 nm, 80 nm, 85 nm, 90 nm, 95 nm, 100 nm or a range consisting of any two of the above values. Coating the surface of the hard carbon material with a carbon layer and controlling the thickness of the carbon coating layer within the above range helps to further reduce sheet surface defects, while further reducing the exposure of sheet pore structures, further improving the first coulombic efficiency of the negative electrode active material, and making the negative electrode active material have a high reversible capacity, thereby improving the energy density and cycle stability of the secondary battery.
[0096] In some embodiments of the present application, in the hard carbon material, the sheet structure contains a first element, and the first element includes any one of Li, Na, K, Rb, Mg, Ca, and Zn. By introducing the first element into the sheet structure of the hard carbon material, active metal ions can be induced to be stored in the hard carbon material, thereby improving the active metal ion storage capacity.
[0097] In some embodiments of the present application, in the hard carbon material, the flaky structure contains a first element, the first element includes any one of Li, Na, K, Rb, Mg, Ca, and Zn, and the content of the first element relative to the total mass of the hard carbon material is 0.01% to 0.9%. Specifically, the content of the first element relative to the total mass of the hard carbon material can be 0.01%, 0.02%, 0.03%, 0.04%, 0.05%, 0.06%, 0.07%, 0.08%, 0.09%, 0.1%, 0.11%, 0.12%, 0.13%, 0.14%, 0.15%, 0.16%, 0.17%, 0.18%, 0.19%, 0.2%, 0.23%, 0.34%, 0.35%, 0.4%, 0.5%, 0.6%, 0.7%, 0.75%, 0.78%, 0.8%, 0.85%, 0.9% or a range consisting of any two of the above values. By regulating the content of the first element in the hard carbon material within the above-mentioned range, the present application can further induce the storage of active metal ions in the hard carbon material, further improving the storage capacity of active metal ions. Applying the hard carbon material of the present application to secondary batteries can help increase the gram capacity of the battery's negative electrode, thereby improving the energy density of the secondary battery.
[0098] In some embodiments of the present application, in the hard carbon material, the specific surface area of the flake material is in the range of 2 to 28 m 2 / g. Specifically, the specific surface area of the sheet material can be 2m 2 / g, 3m 2 / g, 4m 2 / g, 5m 2 / g, 6m 2 / g, 7m 2 / g, 8m 2 / g, 9m 2 / g, 10m 2 / g, 11m 2 / g, 12m 2 / g, 13m 2 / g, 14m 2 / g, 15m 2 / g, 16m 2 / g, 17m 2 / g, 18m 2 / g, 19m 2 / g, 20m 2 / g, 21m 2 / g, 22m 2 / g, 23m 2 / g, 24m 2 / g, 25m 2 / g, 26m2 / g, 27m 2 / g, 28m 2 / g or a range consisting of any two of the above values. If the specific surface area of the hard carbon material is too large, active metal ions will be adsorbed on the surface of the material, and more electrolyte will be consumed to form a stable SEI layer, resulting in a decrease in the first coulombic efficiency of the material. The present application can avoid excessive electrolyte consumption by regulating the specific surface area of the hard carbon material within the above range, while ensuring the formation of a stable SEI, so that the hard carbon material has a higher reversible capacity and a higher first coulombic efficiency, thereby improving the energy density and cycle stability of the secondary battery.
[0099] In some embodiments of the present application, in the hard carbon material, the ID / IG value of the sheet structure is 1.0 to 1.3. Specifically, the ID / IG value of the sheet structure can be 1.0, 1.01, 1.02, 1.03, 1.04, 1.05, 1.06, 1.07, 1.08, 1.09, 1.1, 1.13, 1.15, 1.16, 1.2, 1.23, 1.25, 1.27, 1.3 or a range consisting of any two of the above values. ID is the peak area of the D peak in the Raman spectrum of the hard carbon material, and IG is the peak area of the G peak in the Raman spectrum of the hard carbon material. The ID / IG value of the hard carbon material provided in the present application is regulated within the above range, so that the hard carbon material has a suitable degree of defects, which can further promote ion adsorption and bonding, while reducing the irreversible capacity loss caused by a high degree of defects, thereby helping to improve the gram capacity of the hard carbon material.
[0100] According to the second aspect of the present application, the present application further provides a negative electrode plate, the negative electrode plate comprising a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector, the negative electrode active material layer comprising a negative electrode active material, the negative electrode active material comprising any hard carbon material described in the first aspect of the present application. The negative electrode plate comprising the above hard carbon material has high capacity, good interface adhesion and high compaction density, and is applied to a secondary battery, which can improve the energy density of the secondary battery while improving the cycle performance and rate performance of the secondary battery.
[0101] In some embodiments of the present application, the negative electrode active material includes any hard carbon material and graphite material described in the first aspect of the present application. Graphite generally has a higher compaction density, but the specific capacity of graphite is low and the rate performance is poor. The hard carbon material has a higher specific capacity, but the compaction density is relatively low. The present application obtains a negative electrode material with both high capacity and high compaction by compounding the hard carbon material with the graphite material, and obtains a negative electrode active material layer with both high capacity and high compaction density. Ordinary granular hard carbon is not conducive to the compounding of hard carbon materials with negative electrode active materials such as graphite. The flaky hard carbon material provided by the present application increases the contact between hard carbon particles and between hard carbon and graphite particles, which is beneficial to reduce the electrode sheet resistance and further improves the rate performance of the negative electrode active material.
[0102] In some embodiments of the present application, the negative electrode active material includes any hard carbon material and graphite material described in the first aspect of the present application, and the mass percentage of the hard carbon material is 0.1% to 99.9% based on the total mass of the negative electrode active material. Specifically, based on the total mass of the negative electrode active material, the mass percentage of the hard carbon material can be 0.1%, 0.5%, 1.0%, 5.0%, 10.0%, 15.0%, 20.0%, 25.0%, 30.0%, 35.0%, 40.0%, 45.0%, 50.0%, 55.0%, 60.0%, 65.0%, 70.0%, 75.0%, 80.0%, 85.0%, 90.0%, 95.0%, 99.9% or a range consisting of any two of the above values. The present application regulates the relative proportion of flaky hard carbon and graphite in the composite electrode. By regulating the mass percentage of the hard carbon material in the negative electrode active material layer within the scope of the present application, the compaction density of the negative electrode active material layer can be optimized, thereby improving the energy density, rate performance and cycle retention rate of the secondary battery.
[0103] In some embodiments of the present application, the compaction density of the negative electrode active material layer is in the range of 1.0 to 1.9 g / cm 3 Specifically, the compaction density of the negative electrode active material layer can be 1.0 g / cm 3 , 1.05g / cm 3 , 1.1g / cm 3 , 1.15g / cm 3 , 1.2g / cm 3 , 1.25g / cm 3 , 1.3g / cm 3 , 1.35g / cm 3 , 1.4g / cm 3 , 1.45g / cm 3 , 1.5g / cm 3 , 1.55g / cm3 , 1.6g / cm 3 , 1.65g / cm 3 , 1.7g / cm 3 , 1.75g / cm 3 , 1.8g / cm 3 , 1.85g / cm 3 , 1.90g / cm 3 Or it is a range consisting of any two of the above values. By adjusting the compaction density of the negative electrode active material layer within the above range, the content of the negative electrode active material per unit area can be increased, thereby increasing the energy density of the secondary battery.
[0104] According to the third aspect of the present application, the present application provides a secondary battery, which includes the negative electrode sheet provided by any one embodiment of the second aspect of the present application. The secondary battery including the negative electrode sheet has high energy density and good cycle performance.
[0105] The secondary battery of the present application also includes a positive electrode sheet. The present application has no particular restrictions on the positive electrode sheet, as long as the purpose of the present application can be achieved. For example, the positive electrode sheet includes a positive current collector and a positive active material layer arranged on at least one surface of the positive current collector. For example, the positive current collector may include a metal foil or a composite current collector, etc. For example, the metal foil is aluminum foil. In some embodiments, the secondary battery is a lithium-ion battery, and the positive electrode active material may include a lithium transition metal oxide, and the lithium transition metal oxide may include but is not limited to at least one of lithium iron phosphate, lithium-rich manganese-based materials, lithium cobalt oxide (LiCoO2), lithium iron manganese phosphate or lithium titanate.
[0106] The present application has no particular limitation on the thickness of the positive electrode current collector and the positive electrode active material layer, as long as the purpose of the present application can be achieved. For example, the thickness of the positive electrode current collector is 5 μm to 20 μm, preferably 6 μm to 18 μm.
[0107] The secondary battery of the present application also includes an electrolyte. In one embodiment, the electrolyte includes a lithium salt and a non-aqueous solvent. The present application has no particular limitation on the concentration of the lithium salt in the electrolyte, as long as the purpose of the present application can be achieved.
[0108] The secondary battery of the present application also includes a diaphragm to separate the positive electrode plate and the negative electrode plate, prevent the internal short circuit of the secondary battery, allow the electrolyte ions to pass freely, and do not affect the electrochemical charge and discharge process. The present application has no special restrictions on the diaphragm, as long as the purpose of the present application can be achieved. For example, the material of the diaphragm can include but is not limited to polyethylene (PE), polypropylene (PP), polytetrafluoroethylene-based polyolefin (PO) diaphragms, polyester films (such as polyethylene terephthalate (PET) films), cellulose films, polyimide films (PI), polyamide films (PA), spandex or aramid films, etc. At least one of the above.
[0109] The secondary battery of the present application also includes a packaging bag for containing a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte, as well as other components known in the art in the secondary battery, and the present application does not limit the above-mentioned other components. The present application does not specifically limit the packaging bag, and it can be a packaging bag known in the art, as long as it can achieve the purpose of the present application. For example, an aluminum-plastic film packaging bag can be used.
[0110] The secondary battery of the present application is not particularly limited, and may include any device that undergoes an electrochemical reaction. In one embodiment of the present application, the secondary battery may include, but is not limited to, a lithium ion battery, a sodium ion battery, a lithium polymer secondary battery, or a lithium ion polymer secondary battery.
[0111] According to a fourth aspect of the present application, the present application provides an electronic device, which includes the secondary battery provided by any one embodiment of the third aspect of the present application. The electronic device including the secondary battery has a long service life.
[0112] The electronic device of the present application is not particularly limited, and it can be any electronic device known in the prior art. In some embodiments, the electronic device can include but is not limited to a laptop computer, a pen-input computer, a mobile computer, an electronic book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini-disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power-assisted bicycle, a bicycle, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera, a large household battery or a lithium-ion capacitor, etc.
[0113] Example
[0114] The following examples and comparative examples are given to more specifically describe the embodiments of the present application. Various tests and evaluations were performed according to the following methods. In addition, unless otherwise specified, "parts" and "%" are based on mass.
[0115] The test methods used in the following examples and comparative examples are as follows:
[0116] 1. Scanning electron microscope (SEM) test
[0117] A scanning electron microscope tester (instrument model: ZEISSSEM) was used to observe the microstructure of the prepared hard carbon material and take SEM photos; and the measurement function of the scanning electron microscope was used to measure the length (L), width (D1), thickness / height (H1), left arc length (L1), square area length (L2), and right arc length (L3) of each structure in the microstructure of the hard carbon material. The specific testing steps are: use the measurement function of the scanning electron microscope to measure various parameters of a single flaky particle, and statistically record the relevant parameters of ten flaky particles. Finally, the length (L), width (D1), thickness / height (H1), left arc length (L1), square area length (L2), and right arc length (L3) of the final particle are taken as the average value of the ten particles. For cross-section testing, an ion polisher (instrument model IB-09010CP) was used to cut out a smooth cross-section, which was then photographed under a SEM. The principle of ion polishing is that under vacuum conditions, an ion source ionizes argon gas. After acceleration and focusing, high-speed argon ions knock out atoms or molecules on the surface of the sample to achieve ion polishing. The height of the hard carbon material was measured by testing the cross-section of the hard carbon particles.
[0118] 2. Transmission electron microscopy (TEM) test
[0119] A transmission electron microscope (FEI Tecnai F20) was used to observe the carbon coating layer of the hard carbon material, and TEM photos were taken to measure the thickness of the carbon coating layer of the hard carbon material.
[0120] 3. Metal element analysis test
[0121] The sample was digested by a microwave digestion instrument (model CEM-Mars5), and the element content was quantitatively tested using an ICP-OES instrument (instrument model PE7000DV). After the sample was digested into a solution by acid, the liquid sample entered the atomization chamber, and formed an aerosol under the action of the carrier gas, and entered the plasma through the central injection tube to be fully evaporated, dissociated, atomized, ionized and excited, emitting the characteristic spectrum of the element, which was qualitatively determined based on the wavelength of the spectrum, and quantitatively analyzed based on the proportionality of the spectrum intensity to the concentration.
[0122] 4. Small-angle X-ray scattering test
[0123] A small-angle X-ray scattering structure analyzer (instrument model: Nano-inXider) was used to test the change in scattering vector of the sample in the scattering intensity range of 0.01nm-1 to 0.7nm-1, and the closed pore volume in the hard carbon material particles was fitted and analyzed.
[0124] 5. Specific surface area and pore volume test
[0125] The hard carbon material powder was placed in a sample tube and vacuum degassed at 100°C for 12 hours. The adsorption of nitrogen by the hard carbon material under different pressures was tested by ASAP2460-physical adsorption analyzer, and the adsorption and desorption isotherms were plotted. The shape of the pores was determined based on the shape of the hysteresis loop, and the pore size distribution curve of the micropores was fitted using the DFT model, and the specific surface area of the hard carbon material was calculated.
[0126] 6. Raman test
[0127] The Raman spectra of hard carbon materials were tested by Raman spectrometer. The range of 200μm×500μm was selected for testing, and more than 200 points were tested at equal intervals within the range. The test range of each point was 1000cm -1 Up to 2000cm -1 Between; recorded at 1320cm -1 Up to 1370cm -1 The peak between is the D peak, at 1570 cm -1 Up to 1620cm -1 The peak that appears between the two points is the G peak. The intensity ratio of ID / IG at each point is counted, and then the average value of multiple points is calculated as the final intensity ratio of ID / IG.
[0128] 7. Compaction density test of negative electrode active material layer:
[0129] Take a fully discharged lithium-ion battery, disassemble the negative electrode sheet, clean it, dry it, use an electronic balance to weigh the negative electrode sheet with an area of S, record the weight as W1, and use a micrometer to measure the thickness T1 of the negative electrode sheet. Use solvent DMC to wash off the negative active material layer, dry it, measure the weight of the negative current collector, record it as W2, and use a micrometer to measure the thickness T2 of the negative current collector. Calculate the weight W0 and thickness T0 of the negative active material layer set on one side of the negative current collector and the compaction density of the negative active material layer by the following formula. W0 = W1-W2, T0 = T1-T2, then compaction density = W0 / (T0×S).
[0130] 8. Total gram capacity of lithium storage of negative electrode active materials and first efficiency test:
[0131] The first reversible gram capacity of the negative electrode active material from 0V to 2.5V can be obtained by the following test method: take a single-sided coated negative electrode sheet, cut it into a disc with a diameter of 14mm and use it as a working electrode, then use a lithium sheet as a counter electrode, use a porous polyethylene film (provided by Celgard) as a separator, inject electrolyte and assemble to obtain a button battery; first discharge the button battery to 0V with a three-stage small current of 0.05C / 0.01C / 0.005C, and record the first discharge capacity of the button battery; then charge it to 2.5V with a constant current of 0.1C, and record the first charge capacity of the button battery. First efficiency = first charge capacity / first discharge capacity × 100%; the first reversible gram capacity of the negative electrode active material from 0V to 2.5V, that is, the total gram capacity of lithium storage = first charge capacity / mass of negative electrode active material, in units of mAh / g.
[0132] The above-mentioned electrolyte includes a basic solvent and a lithium salt. The basic solvent is obtained by mixing ethylene carbonate (EC) and diethyl carbonate (DEC) in a mass ratio of 1:1. The lithium salt is LiPF6 and the concentration of the lithium salt is 1 mol / L.
[0133] The total gram capacity of lithium storage and the first efficiency test of the comparative example are the same as the total gram capacity of lithium storage and the first efficiency test methods of the above-mentioned hard carbon material.
[0134] 9. Energy density (ED) test
[0135] In an environment of 25°C, the lithium-ion battery is charged at a constant current of 0.2C to a voltage of 4.48V or 3.95V, and then charged at a constant voltage; discharged at a constant current of 0.2C to a voltage of 2V, which is recorded as one cycle, and the discharge capacity C and discharge energy E of the first cycle are recorded; and the length, width and height of the battery at a 50% charge state are tested to obtain the volume Vm of the battery, and the energy density ED=E / Vm; the lithium-ion battery is cycled 500 times with the above charge and discharge process, and the discharge capacity C1 after 500 cycles is tested, and the cycle capacity retention rate=C1 / C.
[0136] 10. Test method for rate performance
[0137] The lithium-ion battery is charged at a constant temperature. First, the fully discharged lithium-ion battery is charged to 4.48V at a constant current of 1C, charged to 0.05C at a constant voltage, and then discharged to 3.0V at a constant current of 1C. The discharge capacity obtained is recorded as capacity A; then it is charged to 4.48V at a constant current of 5C, charged to 0.05C at a constant voltage, and then discharged to 3.0V at a constant current of 1C. The discharge capacity obtained is recorded as capacity B, and B / A is the 5C / 1C rate performance.
[0138] Example 1-1
[0139] <Preparation of negative electrode active material>
[0140] Stearic acid tablet dispersion: weigh 100g of polyoxyethylene polypropylene ether and disperse it in 10L of water. Stir the dispersion at 80°C for 2h until the polyoxyethylene polypropylene ether is completely dispersed, then add 75g of stearic acid melt and continue stirring for 3h until the solution forms a microemulsion. The obtained microemulsion is allowed to stand at room temperature for 24h to obtain a stearic acid tablet dispersion for use; weigh 50g of resorcinol and 66g of formaldehyde, slowly stir them at room temperature to dissolve them in 1000mL of water, then add 1000mL of stearic acid tablet dispersion, then add 1.5g of propylamine, stir for 30min, and then add 5mL 1.5mol / L ammonia solution, heated to 85℃, stirred for 4h; the obtained powder product was centrifuged, filtered, washed and dried, and then used as a precursor; resin curing: the powder product was placed in a programmable temperature-controlled oven under an inert atmosphere, and the temperature was controlled to 90℃ / 1h+110℃ / 1h+130℃ / 1h+150℃ / 1h to ensure that the resin was fully cured; precursor mixing: 100g of the cured powder product and 10g NaOH, mix the two precursors evenly through a mixer; carbonization: place the mixed precursor in a rotary kiln, heat it to the primary calcination temperature T1 = 900 ° C at a heating rate of 5 ° C / min, carbonize for 2 hours, cool down, and obtain the carbonized material after cooling; acid washing and water washing: then wash the collected powder with 1M hydrochloric acid for 12 hours, filter and take the filter residue and wash it with deionized water for 12 hours, filter and dry the filter residue; form a coating layer on the surface: then transfer the dried powder into a nitrogen atmosphere protection furnace, heat it to the vapor deposition temperature T3 = 900 ° C at a heating rate of 5 ° C / min, and then replace the gas atmosphere with a mixed gas of reducing gas methane and argon, the vapor deposition time t3 = 2 hours, disconnect the above mixed gas after the vapor deposition is completed, replace it with nitrogen, and wait for cooling to room temperature to obtain a hard carbon material, that is, a negative electrode active material. Based on the mass of the mixed gas, the mass percentage of reducing gas methane is 10%.
[0141] <Preparation of negative electrode sheet>
[0142] The hard carbon material prepared above was mixed with the binder styrene-butadiene rubber and the thickener sodium carboxymethyl cellulose in a mass ratio of 97:1.5:1.5, and then deionized water was added as a solvent to prepare a negative electrode slurry with a solid content of 40wt%, and stirred evenly. The negative electrode slurry was evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 6μm, and the copper foil was dried at 85°C for 4h to obtain a negative electrode sheet with a single-sided coating of a negative electrode active material layer with a coating thickness of 50μm. After cold pressing, cutting and slitting, it was dried under vacuum conditions at 120°C for 12h to obtain a negative electrode sheet.
[0143] <Preparation of positive electrode sheet>
[0144] The positive electrode active material lithium cobalt oxide, the conductive agent conductive carbon black (Super P), and the binder PVDF are mixed in a mass ratio of 97:1.4:1.6, and N-methylpyrrolidone (NMP) is added as a solvent, stirred evenly, and a positive electrode slurry with a solid content of 72wt% is prepared. The positive electrode slurry is evenly coated on one surface of a positive electrode current collector aluminum foil with a thickness of 13μm, and dried at 85°C to obtain a positive electrode sheet with a single-sided coating of positive electrode active material and a positive electrode active material layer thickness of 80μm. After cold pressing, cutting, and slitting, it is dried at 85°C under vacuum conditions for 4h to obtain a positive electrode sheet.
[0145] <Preparation of Electrolyte>
[0146] In a dry argon atmosphere glove box, basic solvents ethylene carbonate (EC), propylene carbonate (PC), and diethyl carbonate (DEC) were mixed in a mass ratio of EC:PC:DEC=1:1:1, and then 1,3-propane sultone, fluoroethylene carbonate, and succinonitrile were added, dissolved and fully stirred, and then lithium salt LiPF6 was added and mixed evenly to obtain an electrolyte, wherein based on the mass of the electrolyte, the mass percentage of the lithium salt was 12.5%, and the mass percentages of 1,3-propane sultone, fluoroethylene carbonate, and succinonitrile were all 2%.
[0147] <Preparation of Separator>
[0148] A polyethylene film with a thickness of 7 μm was used as the separator.
[0149] <Preparation of lithium-ion batteries>
[0150] The prepared positive electrode sheet, separator, and negative electrode sheet are stacked in order, so that the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, and then wound to obtain an electrode assembly. After welding the pole ear, the electrode assembly is placed in an aluminum-plastic film packaging bag, placed in a vacuum oven at 80°C for 12 hours to remove moisture, and the prepared electrolyte is injected. After vacuum packaging, standing, formation, degassing, shaping and other processes, a lithium-ion battery is obtained.
[0151] Example 1-2
[0152] Based on Example 1-1, the amount of stearic acid tablet dispersion added was adjusted to 500 mL, and the remaining steps and parameters of Example 1-2 were the same as those of Example 1-1.
[0153] Examples 1-3
[0154] Based on Example 1-1, the amount of stearic acid tablet dispersion added was adjusted to 1500 mL, and the remaining step parameters of Example 1-3 were the same as those of Example 1-1.
[0155] Examples 1-4
[0156] Based on Example 1-1, the amount of stearic acid tablet dispersion added was adjusted to 2000 mL, and the remaining step parameters of Example 1-4 were the same as those of Example 1-1.
[0157] Examples 1-5
[0158] Weigh 100g of polyvinylidene chloride (PVDC) powder and 10g of LiOH, and mix the two precursors evenly with a mixer. Place the mixed precursor in a rotary kiln, heat it to the primary calcination temperature T1 = 900°C at a heating rate of 5°C / min, carbonize for 2h, cool it down, and obtain the carbonized material after cooling. Then wash the collected powder with 1M hydrochloric acid for 12h, filter it, and wash the residue with deionized water for 12h, filter it, and dry the residue. Then transfer the dried powder to a nitrogen atmosphere protection furnace, heat it to the vapor deposition temperature T3 = 900°C at a heating rate of 5°C / min, and then replace the gas atmosphere with a mixture of reducing gas methane and argon. The vapor deposition time is t3 = 2h. After the vapor deposition is completed, disconnect the above-mentioned mixed gas and replace it with nitrogen. After cooling to room temperature, obtain a hard carbon material, that is, a negative electrode active material. Based on the mass of the mixed gas, the mass percentage of reducing gas methane is 10%.
[0159] Examples 1-6
[0160] Based on Example 1-5, the precursor was replaced with 100 g polyvinylidene chloride powder and 10 g NaOH, and the remaining parameters of Example 1-6 were the same as those of Example 1-5.
[0161] Examples 1-7
[0162] Based on Example 1-5, the precursor was replaced with 100 g of polyvinylidene chloride powder and 10 g of KOH, and the remaining parameters of Example 1-7 were the same as those of Example 1-5.
[0163] Examples 1-8
[0164] Based on Example 1-5, the precursor was replaced with 100 g of polyvinylidene chloride powder and 10 g of RbOH, and the remaining parameters of Example 1-8 were the same as those of Example 1-5.
[0165] Examples 1-9
[0166] Based on Example 1-2, during the preparation of the stearic acid tablet dispersion, the amount of stearic acid melt added was adjusted to 1 g, and the remaining steps and parameters of Example 1-9 were the same as those of Example 1-2.
[0167] Examples 1-10
[0168] Based on Example 1-2, during the preparation of the stearic acid tablet dispersion, the amount of stearic acid melt added was adjusted to 15 g, and the remaining steps and parameters of Example 1-10 were the same as those of Example 1-2.
[0169] Embodiment 1-11
[0170] Based on Example 1-2, during the resin prepolymerization process, the amount of resorcinol was adjusted to 25 g, the amount of formaldehyde was adjusted to 33 g, and the amount of ammonia solution added was adjusted to 10 mL. The remaining steps and parameters of Example 1-11 were the same as those of Example 1-2.
[0171] Examples 1-12
[0172] Based on Example 1-2, during the resin prepolymerization process, the amount of resorcinol was adjusted to 75 g, the amount of formaldehyde was adjusted to 99 g, and the amount of ammonia solution added was adjusted to 2 mL. The remaining steps and parameters of Example 1-11 were the same as those of Example 1-2.
[0173] Examples 1-13
[0174] Based on Example 1-2, during the precursor mixing process, the amount of NaOH was adjusted to 2 g, and the remaining steps and parameters of Example 1-13 were the same as those of Example 1-2.
[0175] Examples 1-14
[0176] Based on Example 1-2, during the precursor mixing process, the amount of NaOH was adjusted to 20 g, and the remaining steps and parameters of Example 1-14 were the same as those of Example 1-2.
[0177] Comparative Example 1-1
[0178] Coconut shells were used to replace the polyvinylidene chloride powder used in Example 1-5, and 100 g of the mixed coconut shells and 10 g of NaOH were placed in a rotary kiln containing an inner tank for direct carbonization, and the remaining subsequent steps were the same as those in Example 1-5.
[0179] Comparative Example 1-2
[0180] The commercially purchased artificial graphite was heated to 700°C in a rotary furnace under 10% C2H2 gas and maintained for 2 hours, and then the gas was switched to N2 gas and the final graphite material was obtained after natural cooling.
[0181] Comparative Examples 1-3
[0182] Based on Example 1-2, the step of adding stearic acid tablet dispersion, propylamine and ammonia water was removed, that is, 50 g of resorcinol and 66 g of formaldehyde were directly weighed, slowly stirred at room temperature to dissolve them in 1000 mL of water, heated to 85°C, and stirred for 4 hours; the remaining subsequent steps were the same as in Example 1-2.
[0183] Comparative Examples 1-4
[0184] Based on Example 1-2, the stearic acid tablet dispersion was replaced with stearic acid, that is, 50 g of resorcinol and 66 g of formaldehyde were weighed, slowly stirred at room temperature to dissolve them in 1000 mL of water, and then 1000 mL of stearic acid was added (stearic acid was directly added to water and stirred and dispersed before adding), followed by adding 1.5 g of propylamine. After stirring for 30 minutes, 5 mL of 1.5 mol / L ammonia solution was added, the temperature was raised to 85°C, and stirred for 4 hours; the remaining subsequent steps were the same as those in Example 1-2.
[0185] Example 2-1
[0186] <Preparation of negative electrode active material>
[0187] The commercially purchased artificial graphite was heated to 700°C in a rotary furnace under 10% C2H2 gas and maintained for 2 hours, and then the gas was switched to N2 gas and the final graphite material was obtained after natural cooling.
[0188] <Preparation of negative electrode sheet>
[0189] The hard carbon material prepared in Example 1-2 and the graphite material prepared in Example 2-1 were mixed in a mass ratio of 10:90 to prepare a negative electrode active material, and then the prepared negative electrode active material was mixed with a binder of styrene-butadiene rubber and a thickener of sodium carboxymethyl cellulose in a mass ratio of 97:1.5:1.5, and then deionized water was added as a solvent to prepare a negative electrode slurry with a solid content of 40wt%, and stirred evenly. The negative electrode slurry was evenly coated on one surface of a negative electrode current collector copper foil with a thickness of 6μm, and the copper foil was dried at 85°C for 4h to obtain a negative electrode sheet with a single-sided coating of a negative electrode active material layer with a coating thickness of 50μm. After cold pressing, cutting, and slitting, it was dried under vacuum conditions at 120°C for 12h to obtain a negative electrode sheet.
[0190] The remaining steps of <preparation of positive electrode sheet>, <preparation of electrolyte>, <preparation of separator>, and <preparation of lithium-ion battery> are the same as those in Example 1-1.
[0191] Example 2-2 to Example 2-5
[0192] Except for adjusting the preparation parameters according to Table a, the other parameters of Examples 2-2 to 2-5 are the same as those of Example 2-1.
[0193] Comparative Example 2-1 to Comparative Example 2-5
[0194] Based on Example 2-1, the difference from Example 2-1 is that the hard carbon material used is the hard carbon material prepared in Comparative Example 1-1, and the ratio between the hard carbon material and graphite is adjusted according to Table a, and the rest is the same as Example 2-1.
[0195] Table a
[0196] Group Hard carbon mass ratio Graphite mass ratio Example 2-1 10% 90% Example 2-2 30% 70% Example 2-3 50% 50% Embodiment 2-4 70% 30% Embodiment 2-5 90% 10% Comparative Example 2-1 10% 90% Comparative Example 2-2 30% 70% Comparative Examples 2-3 50% 50% Comparative Examples 2-4 70% 30% Comparative Examples 2-5 90% 10%
[0197] Effect Example 1
[0198] By the above test method, the relevant parameters and relevant properties of the materials prepared in the above Examples 1-1 to 1-14 and Comparative Examples 1-1 to 1-4 were further tested, and the results are shown in Table 1:
[0199] Table 1
[0200]
[0201]
[0202] like Figure 1 As shown, the hard carbon material provided by the present application is in the form of flakes. According to the results presented in Table 1, it can be seen that the flaky hard carbon material with a specific morphology provided by the present application as a negative electrode active material has a higher lithium storage capacity in the range of 0V to 2.5V, and the negative electrode active material provided by the present application has a higher gram capacity and reversible capacity. The morphology of the hard carbon material provided by the present application is mainly affected by the sample synthesis conditions, mainly including the influence of the template (stearic acid flake dispersion) and the activator (NaOH, LiOH, KOH, RbOH). When the template is less, the prepared hard carbon material is longer; when the template increases, the prepared hard carbon material becomes shorter and thinner. When the type of activator changes, the higher the activity of the activator, the smaller the overall size of the prepared material particles. The present application adjusts the relevant parameters of the hard carbon material by adjusting the corresponding process parameters, so that the material's gram capacity, first efficiency and other performance are significantly improved.
[0203] at the same time, Figure 2 The negative electrode active material of Comparative Example 1-1 is shown to have a Li / Li ratio of 0V to 2.5V with lithium metal as the counter electrode. + The charge and discharge curves in the potential range of Figure 2 It can be seen that in the potential range of Li / Li+ of 0V to 0.2V, the specific capacity of the negative electrode active material of Comparative Example 1-1 is 233mAh / g; in the potential range of Li / Li+ of 0V to 2.5V, the specific capacity of the negative electrode active material of Comparative Example 1-1 is 482mAh / g.
[0204] Figure 3The charge and discharge curves of the negative electrode active material prepared in Example 1-2 with lithium metal as the counter electrode in the Li / Li+ potential range of 0V to 2.5V are shown; Figure 3 It can be seen that within the potential range of Li / Li+ of 0V to 0.2V, the specific capacity of Example 1-2 is 483mAh / g; within the potential range of Li / Li+ of 0V to 2.5V, the specific capacity of the negative electrode active materials of Example 1-2 is 720mAh / g, respectively, indicating that the negative electrode active materials of Example 1-2 have high specific capacity, wherein the negative electrode active materials of Example 1-2 have a stable low potential platform, and exhibit higher energy density when applied to full batteries.
[0205] Effect Example 2
[0206] By the above test method, the compaction density of the negative electrode active material layer and the related performance of the lithium ion battery corresponding to the above Examples 1-2, 1-7, 2-1 to 2-5 and Comparative Examples 2-1 to 2-5 were further tested, and the results are shown in Table 2:
[0207] Table 2
[0208]
[0209]
[0210] Table 2 shows the compacted density and lithium-ion battery data of the negative electrode active material layer of Example 1-2, Example 1-7, Example 2-1 to Example 2-5, and Comparative Example 2-1 to Comparative Example 2-5. It can be seen from Table 2 that the compacted density of the negative electrode active material is significantly affected by the composition of the active material. Generally, graphite has a higher compacted density, but the gram capacity of graphite is low and the rate performance is poor. The hard carbon material has a higher gram capacity, but the compacted density is relatively low. The present application further compounded the hard carbon material with a specific morphology with the graphite material to obtain a negative electrode material with both high capacity and high compaction. However, according to the data in Table 2, it can be further seen that the use of ordinary granular hard carbon and graphite is not conducive to compounding. The use of the flaky hard carbon material provided by the present application and the graphite material for compounding increases the contact between the hard carbon particles and between the hard carbon and the graphite particles, which is beneficial to reduce the electrode sheet resistance and further improve the rate performance of the negative electrode active material. It can be seen from Examples 2-1 to 2-5 that by adjusting the relative proportions of flaky hard carbon and graphite in the composite electrode, the compaction density of the negative electrode active material layer can be further optimized, thereby improving the energy density, rate performance, cycle retention rate and other properties of the secondary battery.
[0211] at the same time, Figure 4The charge and discharge curves of the negative electrode active material prepared in Example 2-3 with lithium metal as the counter electrode in the Li / Li+ potential range of 0V to 2.5V are shown; Figure 4 It can be seen that there are obvious steps in the potential range of 0-0.2V, but it is different from the charge and discharge curves of traditional graphite and hard carbon, which proves that the capacity of graphite and hard carbon can be effectively exerted, and there is good interface conduction between particles. In the potential range of Li / Li+ from 0V to 0.2V, the specific capacity of Example 2-3 is 386mAh / g; in the potential range of Li / Li+ from 0V to 2.5V, the specific capacity of the negative active material of Example 2-3 is 552mAh / g, respectively, indicating that the negative active material of Example 2-3 has a high specific capacity, wherein the negative active material of Example 2-3 has a stable low potential platform. In addition, due to the compounding of graphite and hard carbon, Example 2-3 makes the negative active material also have a high compaction density, so that the negative active material described in Example 2-3 is applied to the full battery to show higher energy density, rate performance and cycle retention rate.
[0212] It is to be understood that the present application is described by some embodiments, and it is known to those skilled in the art that various changes or equivalent substitutions may be made to these features and embodiments without departing from the spirit and scope of the present application. In addition, under the guidance of the present application, these features and embodiments may be modified to adapt to specific circumstances and materials without departing from the scope of the present application. Therefore, the present application is not limited by the specific embodiments disclosed herein, and all embodiments falling within the scope of the claims of the present application are within the scope protected by the present application.
Claims
1. A hard carbon material, characterized in that: The hard carbon material is in a sheet-like structure, the length of the sheet-like structure is L, the width of the sheet-like structure is D1, wherein L satisfies: 2μm≤L≤16μm; and D1 satisfies: 0.1μm≤D1≤3μm.
2. The hard carbon material according to claim 1, characterized in that The hard carbon material satisfies at least one of the following conditions: (1) The length L of the sheet structure satisfies: 2 μm ≤ L ≤ 15 μm; (2) The width D1 of the sheet structure satisfies: 0.5 μm ≤ D1 ≤ 1.9 μm; (3) The height H1 of the sheet structure satisfies: 0.02 μm ≤ H1 ≤ 2.5 μm; or, 0.05 μm ≤ H1 ≤ 1.9 μm; (4) The ratio of the length L of the sheet structure to the height H1 of the sheet structure satisfies: 2.5≤L / H1≤750; or, 2.5≤L / H1≤200; (5) The ratio of the width D1 of the sheet structure to the height H1 of the sheet structure satisfies: 1≤D1 / H1≤12.
3. The hard carbon material according to any one of claims 1 to 2, characterized in that: The length L of the sheet structure consists of three parts: the left arc length L1, the square area length L2, and the right arc length L3. L1, L2, and L3 satisfy the following relationship: 2μm≤L1+L2+L3≤16μm, 0.01μm≤L1≤1.5μm, 10≤L2 / L1≤80.
4. The hard carbon material according to claim 3, characterized in that The hard carbon material satisfies at least one of the following conditions: (6) 2μm≤L1+L2+L3≤15μm; (7) 0.05 μm ≤ L1 ≤ 1 μm; (8)11≤L2 / L1≤38.
5. The hard carbon material according to claim 3, characterized in that The hard carbon material satisfies at least one of the following conditions: (9) 0.8 μm ≤ L2 ≤ 15 μm; or, 1.9 μm ≤ L2 ≤ 13 μm; (10) 0.05 μm ≤ L3 ≤ 1.5 μm; or, 0.05 μm ≤ L3 ≤ 1 μm.
6. The hard carbon material according to claim 1, characterized in that The closed pore volume of the sheet structure is 0.01 to 0.4 cm 3 / g; or, the closed pore volume of the sheet structure is 0.05 to 0.28 cm 3 / g.
7. The hard carbon material according to claim 1, characterized in that The hard carbon material satisfies at least one of the following conditions: (11) The surface of the sheet structure also has a carbon coating layer; (12) The surface of the sheet structure also has a carbon coating layer, and the thickness of the carbon coating layer ranges from 20 to 100 nm; (13) The sheet structure contains a first element, and the first element includes any one of Li, Na, K, Rb, Mg, Ca, and Zn; (14) The sheet structure contains a first element, the first element includes any one of Li, Na, K, Rb, Mg, Ca, and Zn; the content of the first element relative to the total mass of the hard carbon material is 0.01% to 0.9%; (15) The specific surface area of the sheet structure is in the range of 2 to 28 m 2 / g; (16) The ID / IG value of the sheet structure is 1.0 to 1.
3.
8. A secondary battery, comprising a positive electrode sheet, a negative electrode sheet and an electrolyte, characterized in that: The negative electrode sheet comprises a negative electrode current collector and a negative electrode material layer located on at least one surface of the negative electrode current collector, the negative electrode active material layer comprises a negative electrode active material, and the negative electrode active material comprises the hard carbon material according to any one of claims 1 to 7; or, The negative electrode active material comprises the hard carbon material and graphite material according to any one of claims 1 to 7; and / or, based on the total mass of the negative electrode active material, the mass percentage of the hard carbon material is 0.1% to 99.9%.
9. The secondary battery according to claim 8, characterized in that: The compaction density of the negative electrode active material layer is in the range of 1.0 to 1.9 g / cm 3 .
10. An electronic device, characterized in that: The electronic device includes the secondary battery as claimed in claim 9.
Citation Information
Patent Citations
Composite material and preparation method thereof, electrochemical device and electronic device
CN115425215A
Hard carbon material with lamellar structure
CN118825241A
Negative electrode active material, negative electrode active slurry, negative electrode plate and preparation method
CN118943363A
Cited By
Hard carbon material and preparation method thereof, negative electrode, battery and electric equipment
CN120149404A
Hard carbon material and preparation method thereof, negative electrode, battery and electrical equipment
CN120149404B
Silicon-carbon composite material, negative pole piece, secondary battery and electric device
CN122025616A
Hard carbon material, negative pole piece, secondary battery and electric device
CN122025631A